2021
DOI: 10.2139/ssrn.3830216
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Bias in Intertemporal Choice

Abstract: Many intertemporal trade-offs are unbalanced: while the advantages of options are concentrated in a few periods, the disadvantages are dispersed over numerous periods. We provide novel experimental evidence for "concentration bias", the tendency to overweight advantages that are concentrated in time. Subjects commit to too much overtime work that is dispersed over multiple days in exchange for a bonus that is concentrated in time: concentration bias increases subjects' willingness to work by 22.4% beyond what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…How these forces interact with the complexity of the choice set is an open question. This has important economic implications in light of conflicting evidence on range weighting; while I document consistent evidence for relative thinking in a simple choice environment, other work has supported the predictions of focusing in more complex settings, such as intertemporal choice (Dertwinkel‐Kalt et al (2021)). Whether a trip to the grocery store, buying car insurance, or online shopping are simple or complex decisions is unclear.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…How these forces interact with the complexity of the choice set is an open question. This has important economic implications in light of conflicting evidence on range weighting; while I document consistent evidence for relative thinking in a simple choice environment, other work has supported the predictions of focusing in more complex settings, such as intertemporal choice (Dertwinkel‐Kalt et al (2021)). Whether a trip to the grocery store, buying car insurance, or online shopping are simple or complex decisions is unclear.…”
Section: Discussionmentioning
confidence: 63%
“…A prior experiment by Andersson, Carlson, and Wengström (2021) found mixed evidence of range‐dependent weighting in an intertemporal choice context: they showed that expanding the range of immediate payments leads to more impatient choices, but expanding the range of future payments does not induce more patient choices. A contemporaneous study by Dertwinkel‐Kalt et al (2021) finds evidence for a bias toward payments concentrated in a single period—a behavior consistent with focusing 1 . My results do not necessarily contradict this evidence.…”
Section: Introductionmentioning
confidence: 80%
“…This could arise, for example, through a preference for lumpy consumption goods(Besley et al, 1993) or for indivisible investment opportunities(Field et al, 2013). It could also arise through a 'concentration bias'(Kőszegi and Szeidl, 2012;Dertwinkel-Kalt et al, 2017) -though our results on use of the lumpsum, presented shortly, suggest that this mechanism, even if relevant in this context, would be operating in addition to the mechanisms of lumpy consumption and lumpy investment.…”
mentioning
confidence: 67%
“…¹Other research in economics on memory that does not focus on associative recall includes work on heuristics (Wilson, 2014), the role of personal experiences (Schwerter and Zimmermann, 2019;Herz and Taubinsky, 2017;Malmendier and Nagel, 2015) and motivated (self-serving) memory (Zimmermann, forthcoming; Carlson et al, 2018;Huffman et al, 2018). More broadly, our paper also relates to the recent experimental literature on bounded rationality, in particular work that has focused on the microfoundations behind behavioral anomalies (Enke and Zimmermann, 2019;Enke, 2017;Enke and Graeber, 2019;Esponda and Vespa, 2016;Martínez-Marquina et al, 2017;Dertwinkel-Kalt et al, 2017;Frydman and Jin, 2018;Hartzmark et al, 2019).…”
Section: Introductionmentioning
confidence: 93%